Basic Services at Primary Health Care based on Satisfaction Levels - Epi Saptaningrum; Joni Siswanto; Ajeng Titah Normawati (Program Studi Keperawatan Blora, Politeknik Kesehatan Kementerian Kesehatan Semarang, 2021)
Research background : Primary Health Care one of the public health services has the main task of providing community health development and basic health services, through increasing public access to health services with a priority for promotive and preventive efforts combined in a balanced manner with curative and rehabilitative efforts. (MOH, 2003). One of the indicators of the success of individual health services at primary health care is patient satisfaction. Satisfaction according to Kotler (in Supranto, 2001) is defined as a post-consumption assessment, that a selected product can meet or exceed consumer expectations, thereby affecting the decision-making process for repurchasing the same product.Research purposes: To determine the level of patient satisfaction with basic health services in Primary Health Care throughout Blora Regency which is seen from the dimensions: responsiveness (responsiveness), reliability (reliability), assurance (assurance), empathy (empathy) and tangible (direct evidence).Research Methods: Design This study was a cross-sectional descriptive survey, conducted in 10 primary health care included in the Blora Regency area. The research subjects were inpatients and outpatients. Samples were taken as many as 300 respondents. The sampling technique in this study was cluster and random sampling in the selection of health centers and the selection of respondents using accidental sampling. Data were collected using a questionnaire consisting of 42 question items. To analyze data using a frequency distribution using a computerResearch Discusion : shows the tendency of patients to be satisfied and very satisfied with the services provided by the health center. Although few are dissatisfied. However, from one puskesmas to another varies in the level of satisfaction.Conclusion: Patients are more satisfied and very satisfied than those who are less satisfied with the services of health workers at the primary health care